Injection of concentrated growth factors from plasma for treating large chronic lower-extremity ulcers defects - Zhang, Zhiqiang; Cao, Nan; Zuo, Chaoqi; Guo, Xuan; Wu, Yilei; Liu, Yongxia; Liu, Guoyan; Wang, Xueqing; Zhou, Shengji; Wang, Haixia; Zhang, Guangliang (Frontiers in Bioengineering and Biotechnology, 2025)
The treatment of chronic lower-extremity ulcers is challenging, with a high ulcer recurrence rate.In chronic wounds, the healing process is stagnated in the inflammatory phase, characterized by persistent activation of the innate immune response. Compared with normal wounds, its environment is highly changed, with the downregulation of growth factor (GF) receptors because of resident low-mitogenic cells. Recently, the use of autologous growth factors has been shown to improve wound healing. We used concentrated growth factors extracted from plasma to treat chronic lower-extremity ulcers. The patients were treated with injections of concentrated growth factors extracted from autologous blood plasma. The wound condition was evaluated five days after each injection. The five patients received five injections of concentrated growth factors once a week. After two weeks, the area of the wound reduced, and the lipodermatosclerosis and abnormal pigmentation significantly improved. The wound was fully epithelialized after treatment. Injection of concentrated growth factors extracted from plasma may effectively treat chronic lower-extremity ulcers. However, the sample size may be relatively small, and we plan to continue collecting additional cases to minimize potential bias.